ANALYSIS OF PHONOLOGICAL ERRORS IN MAHARAH KALAM PRESENTATION OF NAHWU WADHIFI BOOK - Tasha Ayu Azzahra; M. Rizki Hi Aman; Nada Nabilah Syafiqoh (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
The lack of attention to the Maharah Kalam has made many Arabic language scholars unable to communicate using Arabic. Insufficient self-confidence, fear of being wrong in terms of rules and pronunciation create obstacles for students to speak Arabic, therefore an It is necessary to analyze linguistic faults so that Arabic pronunciation pays more attention and in order to avoid mistakes in Arabic pronunciation. The purpose of this study is to outline the types of phonological errors in Maharah Kalam, as well as to analyze phonological errors in student Maharah Kalam. This research is field research and is a qualitative descriptive study that employs a linguistic error analysis approach. Ways for gathering data that involve observation and recording. This observation is carried out by paying attention to students' speech and noting any grammar mistakes. Documentation is completed using recording technology. According to the study's findings, consonant sound alterations represent faults at the phonological (phoneme) level, including: changes in consonant /ث/ to consonant /س/, consonant /ع/ to consonant /أ/, consonant /ص/ becomes a consonant /س/. The other errors are errors in reducing phoneme sounds, phonological mistakes at the level of syntax, and phonological mistakes at the morphological level. It can be concluded that there are several errors in language and the factor causing language errors is a lack of attention to the language rules that should be applied. Apart from that, there is the influence of the student's mother tongue or second language, and the influence of the environment, both formal and informal, as well as the lack of application of Arabic. Several causal factors have a big influence on students' phoneme pronunciation errors. This research can provide a new platform for Arabic speakers to always pay attention to Arabic rules when speaking.